2000
DOI: 10.1002/1521-4141(2000012)30:12<3487::aid-immu3487>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Central tolerance induction in natural immunoglobulin-allotype-specific T cells

Abstract: While self toleance is induced to IgGb2a in Ighb / b mice, an anti‐IgGb2a T cell activity emerges in their Igha / a congenic counterparts. This activity is revealed by postnatal transfer of Igha / a T splenocytes into Igha / b F1, in which total suppression of IgG2ab expression is established. Here, we sought to determine whether the natural T cell unresponsiveness to IgG2ab in Ighb / b mice involved a central tolerance. Based on the kinetics of postnatal thymic Cγ2ab gene expression in Ighb / b mice, we trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Bogen et al (40) found that T cells specific for a V region peptide from the light chain of MOPC-315 underwent thymic deletion in mice that either expressed the cognate Ig or that were injected with soluble antibody at a high concentration. These results are consistent with others suggesting that wild-type IgG2a b -specific T cells attain tolerance in the thymus (41). In contrast, Granucci et al (7) found that IgG2a b -specific T cells from a TCR Tg mouse failed to undergo negative selection in mice endogenously expressing IgG2a b .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bogen et al (40) found that T cells specific for a V region peptide from the light chain of MOPC-315 underwent thymic deletion in mice that either expressed the cognate Ig or that were injected with soluble antibody at a high concentration. These results are consistent with others suggesting that wild-type IgG2a b -specific T cells attain tolerance in the thymus (41). In contrast, Granucci et al (7) found that IgG2a b -specific T cells from a TCR Tg mouse failed to undergo negative selection in mice endogenously expressing IgG2a b .…”
Section: Discussionsupporting
confidence: 92%
“…Evidence for central CD4 ϩ T cell tolerance to Ig sequences has been reported by several groups (38)(39)(40)(41)(42). However, two Tg systems previously developed to address this question yielded contrasting results.…”
Section: Discussionmentioning
confidence: 81%